DigiPolls - (:unkn) unknown (My University, 2026)
DIGIPOLS focuses on the intersection of digital technologies and politics. Its mission is to provide a research environment for pursuing cutting-edge, theory-driven empirical research for advancing the study of how digital technologies are impacting our institutions of governance and how politics shapes the development of these technologies. As an inter-departmental entity, DIGIPOLS pursues an interdisciplinary approach that brings together social scientists and computer scientists conducting complementary research in areas related to DIGIPOLS thematic interests. The lab’s researchers are brought together in the DIGIPOLS Forum, which meets regularly to exchange ideas, discuss best practices and offer strategic input to the four DIGIPOLS research clusters.